Public workers in service of America : a reader - Gooding, Frederick W., Jr.; Yellin, Eric Steven, 1978-; McCartin, Joseph Anthony; Boris, Eileen, 1948- (Urbana : University of Illinois Press, 2023)
"From white-collar executives to mail carriers, public workers meet the needs of the entire nation. Frederick W. Gooding Jr. and Eric S. Yellin edit a collection of new research on this understudied workforce. Part One begins in the late nineteenth- and early twentieth century to explore how questions of race, class, and gender shaped public workers, their workplaces, and their place in American democracy. In Part Two, essayists examine race and gender discrimination while revealing the subtle contemporary forms of marginalization that keep Black men and Black and white women underpaid and overlooked for promotion. The historic labor actions detailed in Part Three illuminate how city employees organized not only for better pay and working conditions but to seek recognition from city officials, the public, and the national labor movement. Part Four focuses on nurses and teachers to address the thorny question of whether certain groups deserve premium pay for their irreplaceable work and sacrifices or if serving the greater good is a reward unto itself. Contributors: Eileen Boris, Cathleen D. Cahill, Frederick W. Gooding Jr., William P. Jones, Francis Ryan, Jon Shelton, Joseph E. Slater, Katherine Turk, Eric S. Yellin, and Amy Zanoni"--
Part 1. The Politics of Public Work at the Dawn of the Twentieth Century -- Part 2. Good Government Jobs for Whom? -- Part 3. Organizing Public Workers -- Part 4. Public Workers in the Neoliberal Age.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on July 18, 2023).
eBooks on EBSCOhost
Keywords: Civil service -- United States -- History -- 20th century; Discrimination -- Government policy -- United States; Government employee unions -- United States; Collective bargaining -- Government employees -- United States; Neoliberalism -- Political aspects -- United States; Fonction publique -- États-Unis -- Histoire -- 20e siècle.; Néo-libéralisme -- Aspect politique -- États-Unis.; 20th Century; United States; HISTORY; Labor & Industrial Relations; Social Classes; SOCIAL SCIENCE; Civil service; Collective bargaining -- Government employees; Discrimination -- Government policy; Government employee unions; United States; Public administration; Politics and Government; 1900-1999; Electronic books; History